The Metaphysics of Theism: A Classical and Neo-Classical Synthesis - Joshua Reginald Sijuwade (MDPI AG, 2021)
This article aims to provide a metaphysical elucidation of the notion of Theism and a coherent theological synthesis of two extensions of this notion: Classical Theism and Neo-Classical Theism. A model of this notion and its extensions is formulated within the ontological pluralism framework of Kris McDaniel and Jason Turner, and the (modified) modal realism framework of David Lewis, which enables it to be explicated clearly and consistently, and two often raised objections against the elements of this notion can be successfully answered.